THERAPEUTIC ACTION OF HINGU IN RESPIRATORY SYSTEM: A LITERARY REVIEW (International Journal of Ayurveda and Pharma Research, 2021)
Man has been struggling to get remedies for various life-threatening disorders which are common in the day to day life of the busy world. Many lifestyle disorders such as diabetes mellitus, hypertension, dyslipidemia, thyroid dysfunction, respiratory disorders, skin diseases, etc. arise due to incompatible diet, polluted atmosphere, sedentary life style, lack of exercise, lack of proper sleep, etc. Ayurveda, the science of life, advices to follow Dinacharya, Ritucharya, Sadvritta etc for the benefit of the common man to enhance longevity. Ayurveda utilizes the wide range of herbal drugs either as single drug or in combination for the purpose of health care remedies. The phyto constituents present in these drugs play the major role in treating the diseases. Ferula foetida, known as Hingu in Ayurveda has promising therapeutic value due to the presence of chemical constituents like sulphide derivatives, volatile oil etc. Many studies revealed the various pharmacological actions of Hingu such as carminative, antispasmodic, antimicrobial, antioxidant, etc. This review highlights the available information on the drug Hingu by due consideration to the action of Hingu on the respiratory system and the formulations with Hingu as an ingredient as available in the Ayurvedic texts in treating respiratory disorders. Some other aspects are also discussed in the review.